2010
DOI: 10.1186/1757-7241-18-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in severe trauma assessed by RIFLE criteria: a common feature without implications on mortality?

Abstract: BackgroundAcute kidney injury (AKI) has been hard to assess due to the lack of standard definitions. Recently, the Risk, Injury, Failure, Loss and End-Stage Kidney (RIFLE) classification has been proposed to classify AKI in a number of clinical settings. This study aims to estimate the frequency and levels of severity of AKI and to study its association with patient mortality and length of stay (LOS) in a cohort of trauma patients needing intensive care.MethodsBetween August 2001 and September 2007, 436 trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 25 publications
3
64
1
5
Order By: Relevance
“…24 The elongation of the ARF patients in intensive care unit was also reported by another study. 7 Similar to these studies in our study we demonstrated that in AKI group the duration of intensive care stay was 14.6±14.6 days. The stay was longer than non-AKI group.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…24 The elongation of the ARF patients in intensive care unit was also reported by another study. 7 Similar to these studies in our study we demonstrated that in AKI group the duration of intensive care stay was 14.6±14.6 days. The stay was longer than non-AKI group.…”
Section: Discussionsupporting
confidence: 80%
“…Gomez et al reported 50% incidence for ARF in trauma patients and 24% for risk, 18% for injury and 37.8% for failure. 7 Park et al reported the incidence of ARF as 41.3 % on 378 patients. 24 The authors found 25 Cruz et al made a study on 2164 patients and reported 10.8% for ARF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work in the trauma, burn, and TBI populations is more relevant to our cohort. Although not universally demonstrated (24), AKI has been associated with increased mortality in trauma patients. Bihorac and colleagues (15) examined a cohort of 982 adults (average age, 41 years) with severe blunt trauma (82% had an ISS of .25) and found a 26% incidence of AKI by the RIFLE classification.…”
Section: Discussionmentioning
confidence: 99%
“…Em estudo observacional com cerca de 430 pacientes vítimas de politrauma, Gomes et al 3 demonstraram que 50% deles apresentavam IRA e que aqueles com maiores comprometimentos de função renal permaneciam mais tempo Acute Kidney Injury (AKI) in trauma is, in most cases, multifactorial. Factors related to the initial ressuscitation protocol, degree of the systemic inflamatory response to trauma, contrast nephropathy in diagnostic procedures, rhabdomyolysis and abdominal compartment syndrome are some of those factors.…”
Section: Introductionmentioning
confidence: 99%